Negotiating Identity and Language in Child-Naming: Parental Perspectives in Minangkabau–Japanese Intercultural Marriages - Lestari, Imelda Indah; Putri, Darni Enzimar; Rumbardi, Rumbardi (Andalas International Journal of Socio-Humanities, 2025)
This study explores the practice of naming children in Minangkabau–Japanese intercultural families from linguistic and socio-cultural perspectives. A child’s name reflects identity, cultural values, and the ethnic affiliations of parents from two distinct cultural backgrounds. Based on qualitative data from questionnaires, this research reveals naming strategies and the dynamics of identity negotiation involved in the process. The contrasting cultural contexts—Minangkabau as the world’s largest matrilineal society, and Japan with its traditional patrilineal "ie" system—form the backdrop for fundamental differences in views on lineage, family name inheritance, and family role structures. This study discusses how such intercultural couples negotiate these differences in daily life, decision-making, and especially in naming their children, which often reflects cultural and linguistic compromises. The findings indicate tendencies toward acculturation, assimilation, or even the formation of a new hybrid system, enriching discourse in anthropological linguistics and identity studies within multicultural families.